Climate Efficiency for Sugarcane Production in Brazil and its Application in Agricultural Zoning - Oliveira Aparecido, Lucas Eduardo de; Silva Cabral de Moraes, Jose Reinaldo da [UNESP]; Meneses, Kamila Cunha de; Torsoni, Guilherme Botega; Silva e Costa, Cicero Teixeira; Mesquita, Daniel Zimmermann (Springer, 2021)
Climate efficiency is an index that shows quantitative reduction related to production caused by the drought. Using climate efficiency in zoning agricolas sure is a vanguard in agrometeorology. Therefore, we aimed to simulate the climate efficiency for sugarcane production in Brazil and test its use in agricultural zoning. Mean annual air temperature, total annual precipitation, and climate efficiency were the climatic variables used to define suitable areas for sugarcane cultivation. Potential and actual yield was established using the agroecological zone method. Regions with mean annual temperatures between 28 and 38 degrees C, annual precipitations between 1000 and 1500 mm year(-1), and climate efficiency higher than 0.65 were considered climatically suitable for cultivation. The interpolation and crossing of information allowed obtaining the climatic aptitude zoning of sugarcane production for Brazil. Kriging was used as an interpolation method, using the spherical model, one neighbor, and a 0.25 degrees resolution (27.75 km). The Brazilian states were divided into three major groups, according to sugarcane climate efficiency. The most favorable states for sugarcane production had a mean climate efficiency of 0.92. On the other hand, the states with the lowest climate efficiencies presented values of 0.59. Climatic aptitude zoning shows that 24.45% of the Brazilian territory is climatically suitable for sugarcane cultivation. Mato Grosso do Sul State has favorable climatic aptitude in 98% of its territory. The aptitude of productive losses due to climate efficiency is the lowest from January to April in Brazil. The Midwest and Northeast regions have the lowest climate efficiencies from June to September, thus requiring other alternatives, such as irrigation systems for crop maintenance. The use of climate efficiency to elaborate agricultural zoning allows determining with a high accuracy suitable areas for sugarcane cultivation.
Keywords: Simulation models; Climatic zones; Agroclimatic variables; Potential yield; Thornthwaite (1948) climate; Water balance